Estimating the multi-decadal carbon deficit of burned amazonian forests - Camila V J Silva, Luiz E O C Aragão, Paul J Young, Fernando Espirito-Santo, Erika Berenguer, Liana O Anderson, Izaias Brasil, Aline Pontes-Lopes, Joice Ferreira, Kieran Withey, Filipe França, Paulo M L A Graça, Leticia Kirsten, Haron Xaud, Cleber Salimon, Marcos A Scaranello, Bruno Castro, Marina Seixas, Renato Farias and Jos Barlow (My University, 2020)
Wildfires in humid tropical forests have become more common in recent years, increasing the rates of tree mortality in forests that have not co-evolved with fire. Estimating carbon emissions from these wildfires is complex. Current approaches rely on estimates of committed emissions based on static emission factors through time and space, yet these emissions cannot be assigned to specific years, and thus are not comparable with other temporally-explicit emission sources. Moreover, committed emissions are gross estimates, whereas the long-term consequences of wildfires require an understanding of net emissions that accounts for post-fire uptake of CO 2 . Here, using a 30 year wildfire chronosequence from across the Brazilian Amazon, we calculate net CO 2 emissions from Amazon wildfires by developing statistical models comparing post-fire changes in stem mortality, necromass decomposition and vegetation growth with unburned forest plots sampled at the same time. Over the 30 yr time period, gross emissions from combustion during the fire and subsequent tree mortality and decomposition were equivalent to 126.1 Mg CO 2 ha –1 of which 73% (92.4 Mg CO 2 ha –1 ) resulted from mortality and decomposition. These emissions were only partially offset by forest growth, with an estimated CO 2 uptake of 45.0 Mg ha –1 over the same time period. Our analysis allowed us to assign emissions and growth across years, revealing that net annual emissions peak 4 yr after forest fires. At present, Brazil's National Determined Contribution (NDC) for emissions fails to consider forest fires as a significant source, even though these are likely to make a substantial and long-term impact on the net carbon balance of Amazonia. Considering long-term post-fire necromass decomposition and vegetation regrowth is crucial for improving global carbon budget estimates and national greenhouse gases (GHG) inventories for tropical forest countries.
Keywords: wildfires, tropical forests, stem mortality, necromass decomposition, combustion, CO2 uptake, net emissions